Radiogenic heat production in the Coastal Plain Sands of Ipokia, Dahomey Basin, Nigeria - T.A Adagunodo; O.G. Bayowa; M.R. Usikalu; A.I. Ojoawo (MethodsX, 2019)
This study is aimed at establishing the radiogenic heat production in the Benin Formation of Dahomey Basin using in-situ measurements of elemental concentrations of uranium, thorium and potassium over a kaolin deposits in Ifonyintedo, Ipokia LGA, Ogun State. Super-Spec gamma ray spectrometer is used to obtain varied data of naturally occurring radionuclides over eleven different stations in the Coastal Plain Sands at 1 m height above the ground. The mean heat produced by uranium, thorium and potassium are 294.3, 410.5 and 0.001 ρW kg−1 respectively. The total heat produced in the study area varied from 544.0 to 902.1 ρW kg−1, which classified the study area as Low-to-Moderate Heat Production Potential zone. This classification corresponds to the radiogenic heat characteristics of Benin Formation in Niger Delta. • In-situ measurements of three radioisotopes were made over Coastal Plain Sands of Dahomey Basin. • The mean heat produced by uranium, thorium, potassium and the total radiogenic heat are 294.3, 410.5, 0.001 and 704.79 ρW kg−1 respectively. • The study area is characterized by Low-to-Moderate Heat Production Potential. Method name: Radiometrics, Keywords: Ifonyintedo, Dahomey Basin, Radiogenic heat production, Coastal Plain Sands, Thermal conductivity